Galvanostatic Intermittent Titration and Performance Based Analysis of LiNi0.5Co0.2Mn0.3O2 Cathode. Issue 13 (1st January 2017) - Verma, Ankit; Smith, Kandler; Santhanagopalan, Shriram; Abraham, Daniel; Yao, Koffi Pierre; Mukherjee, Partha P.
Abstract : Galvanostatic intermittent titration technique (GITT) – a popular method for characterizing kinetic and transport properties of battery electrodes – is predicated on the proper evaluation of electrode active area. LiNi0.5044 Co0.1986 Mn0.2970 O2 (NCM523) material exhibits a complex morphology in which sub-micron primary particles aggregate to form secondary particle agglomerates. This work proposes a new active area formulation for primary/secondary particle agglomerate materials to better mimic the morphology of NCM532 electrodes. This formulation is then coupled with macro-homogeneous models to simulate GITT and half-cell performance of NCM523 electrodes. Subsequently, the model results are compared against the experimental results to refine the area formulation. A single parameter, the surface roughness factor, is proposed to mimic the change in interfacial area, diffusivity and exchange current density simultaneously and detailed modeling results are presented to provide valuable insights into the efficacy of the formulation.